2011
DOI: 10.4049/jimmunol.1002671
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Signaling Dampens Inflammatory Peritonitis

Abstract: Previous studies implicated the anti-inflammatory potential of the adenosine 2B receptor (A2BAR). A2BAR activation is achieved through adenosine, but this is limited by its very short t1/2. To further define alternative adenosine signaling, we examined the role of netrin-1 during acute inflammatory peritonitis. In this article, we report that animals with endogenous repression of netrin-1 (Ntn1+/−) demonstrated increased cell count, increased peritoneal cytokine concentration, and pronounced histological chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 36 publications
1
78
1
1
Order By: Relevance
“…Previous work also suggested that the administration of netrin 1 inhibits inflammation in several models of animal disease (36,37), but in our CIA mice, an anti-inflammatory effect of netrin 1 was not detected. Indeed, netrin 1 may not always exhibit anti-inflammatory activity, and contradictory results have been reported.…”
Section: Role Of Netrin 1 In Bone Homeostasiscontrasting
confidence: 84%
“…Previous work also suggested that the administration of netrin 1 inhibits inflammation in several models of animal disease (36,37), but in our CIA mice, an anti-inflammatory effect of netrin 1 was not detected. Indeed, netrin 1 may not always exhibit anti-inflammatory activity, and contradictory results have been reported.…”
Section: Role Of Netrin 1 In Bone Homeostasiscontrasting
confidence: 84%
“…Such bidirectional communication involves cytokine-induced neurological responses (16,17), as well as the modulation of the immune response by neurotransmitters and neuronal guidance proteins (4,5,18). Interestingly, whereas in the former case both protective and deteriorative neurologic responses may be triggered by immune-related compounds (15), in the latter there is a preserved correlation of NGPs serving as a stop signal both for axonal migration and for migration of leukocytes, as demonstrated for netrin-1 and RGM-A (4)(5)(6)19). In other words, to date there was only evidence of a protective immune response for NGPs during hypoxia and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown netrin-1 to have anti-inflammatory functions in several conditions, including acute kidney injury, acute experimental colitis, corneal injury, peritonitis, and acute lung injury. 29,33e40 Although the mechanism by which netrin-1 regulates inflammation remains largely unknown, roles in inhibiting immune cell infiltration 34,36,38,39,41 and macrophage polarization 35 and reducing the levels of proinflammatory cytokines and chemokines 29,42 have been reported. On the other hand, netrin-1 has also been shown to be proinflammatory in atherosclerotic plaques, where it inhibits emigration of macrophages from the lesions and promotes macrophage survival.…”
Section: Discussionmentioning
confidence: 99%